2018
DOI: 10.1016/j.jad.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Central bank interest rate decisions, household indebtedness, and psychiatric morbidity and distress: Evidence from the UK

Abstract: Background: Central banks set economy-wide interest rates to meet exclusively economic objectives. There is a strong link between indebtedness and psychiatric morbidity at the individual level, with interest rates being an important factor determining ability to repay debt. However, no prior research has explored whether central bank interest rate changes directly influence mental health, nor whether this varies by levels of indebtedness. Methods: We use British data (N = 93,255) to explore whether the Bank of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Wilkinson (2016) found that having greater objective indicators of wealth did not appear to predict depressive symptoms following the 2008 Great Recession, but subjective indicators such as financial strain did. Boyce et al (2018) found that low interest rates were inversely related to depressive symptoms among persons with high-debt but the relation between interest rates and depressive symptoms did not vary significantly by savings status.…”
Section: 24mentioning
confidence: 81%
See 1 more Smart Citation
“…Wilkinson (2016) found that having greater objective indicators of wealth did not appear to predict depressive symptoms following the 2008 Great Recession, but subjective indicators such as financial strain did. Boyce et al (2018) found that low interest rates were inversely related to depressive symptoms among persons with high-debt but the relation between interest rates and depressive symptoms did not vary significantly by savings status.…”
Section: 24mentioning
confidence: 81%
“…Boyce et al. (2018) found that low interest rates were inversely related to depressive symptoms among persons with high‐debt but the relation between interest rates and depressive symptoms did not vary significantly by savings status.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of local and regional economic development bodies and larger economic institutions (eg, central banks and the International Monetary Fund) for population health is increasingly clear. 19 , 36 , 37 Complexity economics Key ideas Conceives of the economy as a complex system, interacting with other complex systems (such as population health and the environment). The focus is on the uncertainty created by constant changes and the characteristics of non-linearities, feedback loops, tipping points, and emergence.…”
Section: Economic Theories and Schools Of Thoughtmentioning
confidence: 99%
“…The importance of local and regional economic development bodies and larger economic institutions (eg, central banks and the International Monetary Fund) for population health is increasingly clear. 19 , 36 , 37 …”
Section: Economic Theories and Schools Of Thoughtmentioning
confidence: 99%
“…5 From a social and economic policy perspective, central bank decisions about interest rates might also affect health, because research suggests that with each percentagepoint increase in interest rates, up to approximately 20 000 additional cases of psychiatric-morbidity might occur in the UK. 6 The link between poor health and financial difficulties is well known; however, the precise dynamic mechanisms underpinning these complex associations are not understood. Little evidence-based research exists that investigates associations between finance and health.…”
Section: Improving Insights Into Health Care With Data Linkage To Financial Technologymentioning
confidence: 99%